A PLEA FOR LEADERSHIP THEORIES - V. Kessler (Acta Theologica)
This article addresses the challenge of teaching theory to people who view theorising sceptically. This is often the case in the context of leadership trainings. In this article, I critically analyse the trivialisation of leadership, often based on success stories, and offer seven methods to include theory in leadership classes, namely electing students; reversing the order: practice-theory instead of theory-practice; creating aha experiences with theory; selecting “good” theory; pointing out the benefit of a special theory; viewing theories as eye-glasses, and suggesting eye-glasses from different disciplines. I then argue, first, that leadership theory is needed, because real leadership is non-trivial and, secondly, that we need to teach more than one leadership theory, in order to encourage critical thinking.